INOVASI DAERAH DARI PERSEPEKTIF REGULASI, KONSEPTUAL, DAN EMPIR (Tinjauan terhadap pasal Pasal 386 Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah) - Ranggi Ade Febrian (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2018)
In Act No. 23 of 2014 there is a chapter that specifically regulates regional innovation. Mentioned that in the framework of improving the performance of Regional Government, Local Government can innovate. Innovation is all form of renewal in the implementation of Regional Government. Initiatives of innovation can come from regional heads, members of parliament, civil state apparatus, regional apparatus, and community members. This regulation becomes a door for the region to make innovations become increasingly clear. Article 386 of the Regional Government Law expressly states, in the framework of improving the performance of local government administration, local government can innovate. Conceptually Rogers (1961) explains that innovation is an idea, practice, or object that is considered new by the individual one unit of other adoption. The variables affecting the innovation diffusion stage include (1) innovation attributes, (2) types of innovation decisions, (3) communication channels, (4) social system conditions, and (5) the role of change agents. West Java Province serve as an example of a region that successfully implemented local innovation. There are three categories of innovation, namely Governance Governance Innovation, Public Service Innovation, and Sectoral Product Innovation. Governance Innovation Governance, aimed at improving Government performance, apparatus professionalism, and expansion of public participation. While Public Service Innovation is designed to build a quality society and competitive. The Sector Product Innovation is designed to build a robust and equitable economy. This success led to the Governor of West Java awarded as Head of Innovative Region 2017. If West Java Province can apply successful regional innovation, why other regions are still afraid to apply it.